Structural health monitoring of carbon fiber reinforced matrix by the resistance variation method. (October 2020) - Hamdi, Khalil; Aboura, Zoheir; Harizi, Walid; Khellil, Kamel
In this work, electrical resistance change method is used for carbon fiber reinforced thermoplastic polymers damage monitoring. The electrical resistance variation could be an interesting complementary to existing/classical damage monitoring methods. It is extremely attributed to electrical conductivity of composite material and it appears that enhancing the conductivity of materials, by the use of conductive nanofillers in our case, improves their sensitivity to mechanical loading. Carbon fiber reinforced thermoplastic polymers with different nanofillers types and concentrations were manufactured and tested in tensile loading. Concentration of 0 and 8 wt% of carbon black and 2.5 wt% of carbon nanotubes were used with Polyamide 6 sheets as matrix. Nanofillers weakening effect was discussed according to their concentrations and types. The acoustic emission, digital image correlation and in-situ microscopy were also recorded during testing. A correlation between all these signals and the evolution of the electrical resistance of the composites during the tensile loading was performed. It was found that CB enhances sensitivity of carbon fiber reinforced thermoplastic polymers to damage detection, especially delamination. For the carbon nanotubes, results are less promising. A discussion is held about the nanofillers concentration influence.